Proposing a Digital Content Marketing Model for Customer Relationship Management in Beauty Clinics - Devisti, Somayeh; Landaran Esfahani, Saeed; Ghorbani, Hassan (Digital Transformation and Administration Innovation, 2026)
Digital marketing refers to the process of promoting, selling, and delivering products or services through online platforms and digital channels using the internet and electronic devices within the digital environment. One branch of digital marketing is digital content marketing. This form of marketing involves the creation and distribution of valuable and relevant content to engage customers in a way that motivates them to participate in achieving business goals. The aim of digital content marketing is to attract target audiences through diverse strategies and methods, enhance brand presence, and promote sales growth. The primary objective of this research is to develop a digital content marketing model for customer relationship management in beauty clinics in the city of Isfahan. To deeply examine and analyze this topic, the grounded theory method and a qualitative research approach were employed. Data were collected through semi-structured interviews with six specialist physicians. Based on the analysis of the collected data, a proposed model was constructed. The model consists of causal conditions (technological advancement, inclination toward virtual spaces, and responsiveness to customer needs), contextual factors (environmental, managerial, and financial factors), intervening conditions (legal-political issues and technical-content challenges), strategies (customer interaction, content production and management, digital marketing, monitoring and overcoming limitations, adherence to ethical principles), and finally, outcomes (customer development and management, and the growth and success of the clinic). The results of the study indicate that digital content marketing positively affects the performance improvement of beauty clinics in Isfahan. Ultimately, the study provides recommendations to enhance business performance.